DISCRIMINATION AND SOCIAL EXCLUSION AMONG AFGHAN REFUGEES IN PAKISTAN: CHALLENGES AND SOLUTIONS - Aneta Ismail; Ruhma Jamil; Syed Tahir Abbas; Muhammad Arif; Yong Wang; Wang Weihong (International Journal of Contemporary Issues in Social Sciences, 2024)
This research article brings light to the lived realities of Afghan refugees in Quetta, Balochistan which is indeed a multilayered issue, where below the clouds discrimination and social exclusion are the main players. As the paper's qualitative research methodology integrate detailed interviews, dialogues with NGO personnel, as well as participant observations to paint a realistic picture of the day-to-day conditions of refugees, the paper aims to portray a comprehensive picture. The facts show up major hindrances concerning education, employment, healthcare access and constantly mental pressure that come with the legal status insecurity. These notions are then dissected using the theories of social exclusion and intersopee relations, exposing a detailed picture of the situation the refugees are going through. The work suggests applying about the well grounded policies especially improving the public engagement initiatives like legal support and education programs where people have a ground to express their concerns and access information to help them fight the challenge. Through championing for a holistic solution-based approach in addressing discrimination challenges faced by Afghan refugee community in Pakistan, the paper also argues for the preservation of human dignity and strengthening of all the existing rights ensuring meaningful contributions to the migration integration and social cohesion discourse.